2005
DOI: 10.1603/0022-0493-98.1.129
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Early-Season Thrips Management on Reducing the Risks of Spotted Wilt Virus and Suppressing Aphid Populations in Flue-Cured Tobacco

Abstract: The influence of tray drench (TD) treatments, with and without foliar applications of the plant activator acibenzolar-S-methyl (Actigard), was examined in replicated field plots in 2000--2002. TD treatments of Actigard, imidacloprid (Admire), and these two products combined had little effect on seasonal mean thrips populations; however, thrips densities were lower in the Admire-treated plots at 4 and 5 wk after transplanting. Actigard and Admire TD treatments significantly reduced the seasonal incidence of tom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
9
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 13 publications
1
9
0
2
Order By: Relevance
“…Momol et al (2004) also reported a similar reduction in TSW incidence without a consistent increase in marketable fruit yield after seasonlong applications of acibenzolar-S-methyl. Acibenzolar-S-methyl in conjunction with imidacloprid has been shown to be very effective in reducing early season TSW incidence in tobacco (McPherson et al 2005. This plus our results suggest that use of acibenzolar-S-methyl might require the use of an additional thrips reducing tactic to provide signiÞcant reductions in disease incidence.…”
Section: Discussionsupporting
confidence: 61%
“…Momol et al (2004) also reported a similar reduction in TSW incidence without a consistent increase in marketable fruit yield after seasonlong applications of acibenzolar-S-methyl. Acibenzolar-S-methyl in conjunction with imidacloprid has been shown to be very effective in reducing early season TSW incidence in tobacco (McPherson et al 2005. This plus our results suggest that use of acibenzolar-S-methyl might require the use of an additional thrips reducing tactic to provide signiÞcant reductions in disease incidence.…”
Section: Discussionsupporting
confidence: 61%
“…As observed in these trials and other studies, many factors influence the incidence of TSWV in flue-cured tobacco in any given year (4,6,11,12). To be able to compare yields within a year, we included a transgenic K-326 that is not susceptible to TSWV but would be affected by weather and other factors during the growing season.…”
Section: Discussionmentioning
confidence: 99%
“…vesicatoria as early as 3 days after application (16) and significantly increased survival of pepper plants against Phytophthora root and crown rot (10). Studies on the effect of ASM on tomato spotted wilt incidence on tomato and tobacco showed a significant reduction in incidence in combination with other treatments such as reflective mulches and insecticides (12) or with timing of application, such as when applied before transplanting (4,11). Reproduction of the rootknot nematode (Meloidogyne javanica) and the reniform nematode (Rotylenchulus reniformis) was significantly reduced after pineapple plants (Ananas comosus) were treated with ASM (2).…”
mentioning
confidence: 99%
“…TSW also is a serious economic threat to vegetables (Riley and Pappu 2000, Groves et al 2001, Stavisky et al 2002 and peanuts (Brown et al 2002). In fact, TSW has a wide host range that includes several hundred plant species from Ͼ20 families (Mumford et al 1996, McPherson et al 2005b, and many of these host plants are reported as suitable hosts for thrips and TSW in Georgia (Wells et al 2002, McPherson et al 2003a.…”
mentioning
confidence: 99%
“…Several thrips species have been conÞrmed as vectors of TSW in the ßue-cured tobacco farmscape (McPherson et al 2003a(McPherson et al , 2005b, but F. fusca is reported as the predominate species on tobacco foliage (McPherson et al 1999). F. fusca is highly polyphagous and has been reported as a vector of TSW on several host plant species associated with the tobacco farmscape , McPherson et al 2003a.…”
mentioning
confidence: 99%